2016
DOI: 10.1074/jbc.m116.732966
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanism of 17α,20-Lyase and New Hydroxylation Reactions of Human Cytochrome P450 17A1

Abstract: We propose three mechanisms that can involve the FeO 3؉ entity and that explain the 18 O label in the acetic acid, two involving the intermediacy of an acetyl radical and one a steroid 17,20-dioxetane. P450 17A1 was found to perform 16-hydroxylation reactions on its 17␣-hydroxylated products to yield 16,17␣-dihydroxypregnenolone and progesterone, suggesting the presence of an active perferryloxo active species of P450 17A1 when its lyase substrate is bound. The 6␤-hydroxylation of 16␣,17␣-dihydroxyprogesterone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
60
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 88 publications
7
60
0
Order By: Relevance
“…We have shown that P450 17A1 incorporates a single oxygen ( 18 O) atom from molecular oxygen ( 18 O 2 ) into the acetic acid product in the lyase step (ii) when 17 α -hydroxy-[21,21,21- 2 H 3 ]-pregnenolone is used as the substrate. 15 Therefore, in order to determine 18 O-incorporation into pregnenolone by P450 11A1, the derivatized acetic acid product was analyzed for incorporation of one or two 18 O atoms. If the derivatized acetate product contained two 18 O atoms, then the mechanism shown in Scheme 2Ba would be supported.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have shown that P450 17A1 incorporates a single oxygen ( 18 O) atom from molecular oxygen ( 18 O 2 ) into the acetic acid product in the lyase step (ii) when 17 α -hydroxy-[21,21,21- 2 H 3 ]-pregnenolone is used as the substrate. 15 Therefore, in order to determine 18 O-incorporation into pregnenolone by P450 11A1, the derivatized acetic acid product was analyzed for incorporation of one or two 18 O atoms. If the derivatized acetate product contained two 18 O atoms, then the mechanism shown in Scheme 2Ba would be supported.…”
Section: Resultsmentioning
confidence: 99%
“…The detection of the acetate with a single 18 O atom indicates the possibility of some exchange of the C20-oxygen in the 21-carbon steroid products (Scheme 4, 4a to 4b or 16a to 16b ) during the enzyme-coupled assay. However, the LC-MS analysis of the synthetic pyridine acetate standard with no 18 O label (Supporting Information), which was prepared by treating acetic anhydride with the corresponding alcohol, 15 did show the presence of some acetate containing one 18 O atom (0.003% 18 O). Therefore, the source of the mono- 18 O-containing acetate detected in the positive control experiment (Figures 3B and 3C, 18d-1 ) may be from the acetate derived from background acetic acid.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the H 2 O 2 ‐dependent CYPs have been deployed to oxidize non‐native substrates in the presence of decoy molecules . Further, single‐oxygen donors (e.g., periodate and iodosobenzene) are also found to promote CYP‐catalyzed monooxygenation reactions, resulting in a highly reactive ferryl heme π‐cation radical known as compound I . However, few CYPs are known to display such characteristics in the presence of specific chemical compounds.…”
Section: Introductionmentioning
confidence: 99%